A survey on cancer-related nutritional information in Iranian popular magazines - Hovsepyan, Ourfa (J Educ Health Promot, 2015)
BACKGROUND: Due to the wide influence of public media, they become important communication channels for changing health beliefs and behaviors. One of the areas that have gained increased attention in public media is nutritional information. Cancer is one among the diseases related to nutrition. The goal of this study is to do a content analysis of the popular magazines in Iran for nutritional information related to cancer in year 2012–2013. MATERIALS AND METHODS: This is an applied survey performed using content analysis method. The data gathering tool is a checklist designed by the researcher. The statistical population consisted of all of the messages printed in 173 volumes of eight most popular magazines which were selected based on their characteristics by searching the Iranian publication database using certain inclusion and exclusion criteria. The sample size calculated using non-probability – purposive sampling was 295 messages from 96 magazine volumes. RESULTS: Findings showed that prevention trends had the highest (86.8%) and treatment had the lowest (4.7%) frequency in the messages. Pomegranate was the most commonly mentioned preventive food, while mayonnaises were the most commonly mentioned carcinogen and tangerine was the most commonly mentioned food used for cancer treatment. Among the different types of cancer, more than half of the messages (51.2%) mentioned “cancer” as a general term. After that, breast cancer (13.2%) and prostate cancer (10.51%) were the most commonly motioned cancers and messages regarding pancreatic cancer and hormone-related cancers were the least frequent (0.3%). CONCLUSIONS: The findings of this study show that the main goal of these messages was to increase the information provided to the readers, although some doubts regarding the scientific credibility of the claims made in these messages still remain.